Operation on tuples #

We interpret maps ∀ i : Fin n, α i as n-tuples of elements of possibly varying type α i, (α 0, …, α (n-1)). A particular case is Fin n → α of elements with all the same type. In this case when α i is a constant map, then tuples are isomorphic (but not definitionally equal) to Vectors.

Main declarations #

There are three (main) ways to consider Fin n as a subtype of Fin (n + 1), hence three (main) ways to move between tuples of length n and of length n + 1 by adding/removing an entry.

Adding at the start #

• Fin.succ: Send i : Fin n to i + 1 : Fin (n + 1). This is defined in Core.
• Fin.cases: Induction/recursion principle for Fin: To prove a property/define a function for all Fin (n + 1), it is enough to prove/define it for 0 and for i.succ for all i : Fin n. This is defined in Core.
• Fin.cons: Turn a tuple f : Fin n → α and an entry a : α into a tuple Fin.cons a f : Fin (n + 1) → α by adding a at the start. In general, tuples can be dependent functions, in which case f : ∀ i : Fin n, α i.succ and a : α 0. This is a special case of Fin.cases.
• Fin.tail: Turn a tuple f : Fin (n + 1) → α into a tuple Fin.tail f : Fin n → α by forgetting the start. In general, tuples can be dependent functions, in which case Fin.tail f : ∀ i : Fin n, α i.succ.

Adding at the end #

• Fin.castSucc: Send i : Fin n to i : Fin (n + 1). This is defined in Core.
• Fin.lastCases: Induction/recursion principle for Fin: To prove a property/define a function for all Fin (n + 1), it is enough to prove/define it for last n and for i.castSucc for all i : Fin n. This is defined in Core.
• Fin.snoc: Turn a tuple f : Fin n → α and an entry a : α into a tuple Fin.snoc f a : Fin (n + 1) → α by adding a at the end. In general, tuples can be dependent functions, in which case f : ∀ i : Fin n, α i.castSucc and a : α (last n). This is a special case of Fin.lastCases.
• Fin.init: Turn a tuple f : Fin (n + 1) → α into a tuple Fin.init f : Fin n → α by forgetting the start. In general, tuples can be dependent functions, in which case Fin.init f : ∀ i : Fin n, α i.castSucc.

Adding in the middle #

For a pivot p : Fin (n + 1),

• Fin.succAbove: Send i : Fin n to
• i : Fin (n + 1) if i < p,
• i + 1 : Fin (n + 1) if p ≤ i.
• Fin.succAboveCases: Induction/recursion principle for Fin: To prove a property/define a function for all Fin (n + 1), it is enough to prove/define it for p and for p.succAbove i for all i : Fin n.
• Fin.insertNth: Turn a tuple f : Fin n → α and an entry a : α into a tuple Fin.insertNth f a : Fin (n + 1) → α by adding a in position p. In general, tuples can be dependent functions, in which case f : ∀ i : Fin n, α (p.succAbove i) and a : α p. This is a special case of Fin.succAboveCases.
• Fin.removeNth: Turn a tuple f : Fin (n + 1) → α into a tuple Fin.removeNth p f : Fin n → α by forgetting the p-th value. In general, tuples can be dependent functions, in which case Fin.removeNth f : ∀ i : Fin n, α (succAbove p i).

p = 0 means we add at the start. p = last n means we add at the end.

Miscellaneous #

• Fin.find p : returns the first index n where p n is satisfied, and none if it is never satisfied.
• Fin.append a b : append two tuples.
• Fin.repeat n a : repeat a tuple n times.
theorem Fin.tuple0_le {α : Fin 0Type u_1} [(i : Fin 0) → Preorder (α i)] (f : (i : Fin 0) → α i) (g : (i : Fin 0) → α i) :
f g
def Fin.tail {n : } {α : Fin (n + 1)Type u} (q : (i : Fin (n + 1)) → α i) (i : Fin n) :
α i.succ

The tail of an n+1 tuple, i.e., its last n entries.

Equations
Instances For
theorem Fin.tail_def {n : } {α : Fin (n + 1)Type u_1} {q : (i : Fin (n + 1)) → α i} :
(Fin.tail fun (k : Fin (n + 1)) => q k) = fun (k : Fin n) => q k.succ
def Fin.cons {n : } {α : Fin (n + 1)Type u} (x : α 0) (p : (i : Fin n) → α i.succ) (i : Fin (n + 1)) :
α i

Adding an element at the beginning of an n-tuple, to get an n+1-tuple.

Equations
Instances For
@[simp]
theorem Fin.tail_cons {n : } {α : Fin (n + 1)Type u} (x : α 0) (p : (i : Fin n) → α i.succ) :
@[simp]
theorem Fin.cons_succ {n : } {α : Fin (n + 1)Type u} (x : α 0) (p : (i : Fin n) → α i.succ) (i : Fin n) :
Fin.cons x p i.succ = p i
@[simp]
theorem Fin.cons_zero {n : } {α : Fin (n + 1)Type u} (x : α 0) (p : (i : Fin n) → α i.succ) :
Fin.cons x p 0 = x
@[simp]
theorem Fin.cons_one {n : } {α : Fin (n + 2)Type u_1} (x : α 0) (p : (i : Fin n.succ) → α i.succ) :
Fin.cons x p 1 = p 0
@[simp]
theorem Fin.cons_update {n : } {α : Fin (n + 1)Type u} (x : α 0) (p : (i : Fin n) → α i.succ) (i : Fin n) (y : α i.succ) :

Updating a tuple and adding an element at the beginning commute.

theorem Fin.cons_injective2 {n : } {α : Fin (n + 1)Type u} :

As a binary function, Fin.cons is injective.

@[simp]
theorem Fin.cons_eq_cons {n : } {α : Fin (n + 1)Type u} {x₀ : α 0} {y₀ : α 0} {x : (i : Fin n) → α i.succ} {y : (i : Fin n) → α i.succ} :
Fin.cons x₀ x = Fin.cons y₀ y x₀ = y₀ x = y
theorem Fin.cons_left_injective {n : } {α : Fin (n + 1)Type u} (x : (i : Fin n) → α i.succ) :
Function.Injective fun (x₀ : α 0) => Fin.cons x₀ x
theorem Fin.cons_right_injective {n : } {α : Fin (n + 1)Type u} (x₀ : α 0) :
theorem Fin.update_cons_zero {n : } {α : Fin (n + 1)Type u} (x : α 0) (p : (i : Fin n) → α i.succ) (z : α 0) :

Adding an element at the beginning of a tuple and then updating it amounts to adding it directly.

@[simp]
theorem Fin.cons_self_tail {n : } {α : Fin (n + 1)Type u} (q : (i : Fin (n + 1)) → α i) :
Fin.cons (q 0) (Fin.tail q) = q

Concatenating the first element of a tuple with its tail gives back the original tuple

def Fin.consCases {n : } {α : Fin (n + 1)Type u} {P : ((i : Fin n.succ) → α i)Sort v} (h : (x₀ : α 0) → (x : (i : Fin n) → α i.succ) → P (Fin.cons x₀ x)) (x : (i : Fin n.succ) → α i) :
P x

Recurse on an n+1-tuple by splitting it into a single element and an n-tuple.

Equations
Instances For
@[simp]
theorem Fin.consCases_cons {n : } {α : Fin (n + 1)Type u} {P : ((i : Fin n.succ) → α i)Sort v} (h : (x₀ : α 0) → (x : (i : Fin n) → α i.succ) → P (Fin.cons x₀ x)) (x₀ : α 0) (x : (i : Fin n) → α i.succ) :
Fin.consCases h (Fin.cons x₀ x) = h x₀ x
def Fin.consInduction {α : Type u_1} {P : {n : } → (Fin nα)Sort v} (h0 : P Fin.elim0) (h : {n : } → (x₀ : α) → (x : Fin nα) → P xP (Fin.cons x₀ x)) {n : } (x : Fin nα) :
P x

Recurse on a tuple by splitting into Fin.elim0 and Fin.cons.

Equations
Instances For
theorem Fin.cons_injective_of_injective {n : } {α : Type u_1} {x₀ : α} {x : Fin nα} (hx₀ : x₀) (hx : ) :
theorem Fin.cons_injective_iff {n : } {α : Type u_1} {x₀ : α} {x : Fin nα} :
Function.Injective (Fin.cons x₀ x) x₀
@[simp]
theorem Fin.forall_fin_zero_pi {α : Fin 0Sort u_1} {P : ((i : Fin 0) → α i)Prop} :
(∀ (x : (i : Fin 0) → α i), P x) P finZeroElim
@[simp]
theorem Fin.exists_fin_zero_pi {α : Fin 0Sort u_1} {P : ((i : Fin 0) → α i)Prop} :
(∃ (x : (i : Fin 0) → α i), P x) P finZeroElim
theorem Fin.forall_fin_succ_pi {n : } {α : Fin (n + 1)Type u} {P : ((i : Fin (n + 1)) → α i)Prop} :
(∀ (x : (i : Fin (n + 1)) → α i), P x) ∀ (a : α 0) (v : (i : Fin n) → α i.succ), P (Fin.cons a v)
theorem Fin.exists_fin_succ_pi {n : } {α : Fin (n + 1)Type u} {P : ((i : Fin (n + 1)) → α i)Prop} :
(∃ (x : (i : Fin (n + 1)) → α i), P x) ∃ (a : α 0) (v : (i : Fin n) → α i.succ), P (Fin.cons a v)
@[simp]
theorem Fin.tail_update_zero {n : } {α : Fin (n + 1)Type u} (q : (i : Fin (n + 1)) → α i) (z : α 0) :

Updating the first element of a tuple does not change the tail.

@[simp]
theorem Fin.tail_update_succ {n : } {α : Fin (n + 1)Type u} (q : (i : Fin (n + 1)) → α i) (i : Fin n) (y : α i.succ) :

Updating a nonzero element and taking the tail commute.

theorem Fin.comp_cons {n : } {α : Type u_1} {β : Type u_2} (g : αβ) (y : α) (q : Fin nα) :
g Fin.cons y q = Fin.cons (g y) (g q)
theorem Fin.comp_tail {n : } {α : Type u_1} {β : Type u_2} (g : αβ) (q : Fin n.succα) :
g = Fin.tail (g q)
theorem Fin.le_cons {n : } {α : Fin (n + 1)Type u} [(i : Fin (n + 1)) → Preorder (α i)] {x : α 0} {q : (i : Fin (n + 1)) → α i} {p : (i : Fin n) → α i.succ} :
q Fin.cons x p q 0 x p
theorem Fin.cons_le {n : } {α : Fin (n + 1)Type u} [(i : Fin (n + 1)) → Preorder (α i)] {x : α 0} {q : (i : Fin (n + 1)) → α i} {p : (i : Fin n) → α i.succ} :
Fin.cons x p q x q 0 p
theorem Fin.cons_le_cons {n : } {α : Fin (n + 1)Type u} [(i : Fin (n + 1)) → Preorder (α i)] {x₀ : α 0} {y₀ : α 0} {x : (i : Fin n) → α i.succ} {y : (i : Fin n) → α i.succ} :
Fin.cons x₀ x Fin.cons y₀ y x₀ y₀ x y
theorem Fin.range_fin_succ {n : } {α : Type u_1} (f : Fin (n + 1)α) :
= insert (f 0) (Set.range (Fin.tail f))
@[simp]
theorem Fin.range_cons {α : Type u_1} {n : } (x : α) (b : Fin nα) :
def Fin.append {m : } {n : } {α : Type u_1} (a : Fin mα) (b : Fin nα) :
Fin (m + n)α

Append a tuple of length m to a tuple of length n to get a tuple of length m + n. This is a non-dependent version of Fin.add_cases.

Equations
Instances For
@[simp]
theorem Fin.append_left {m : } {n : } {α : Type u_1} (u : Fin mα) (v : Fin nα) (i : Fin m) :
Fin.append u v (Fin.castAdd n i) = u i
@[simp]
theorem Fin.append_right {m : } {n : } {α : Type u_1} (u : Fin mα) (v : Fin nα) (i : Fin n) :
Fin.append u v (Fin.natAdd m i) = v i
theorem Fin.append_right_nil {m : } {n : } {α : Type u_1} (u : Fin mα) (v : Fin nα) (hv : n = 0) :
= u
@[simp]
theorem Fin.append_elim0 {m : } {α : Type u_1} (u : Fin mα) :
Fin.append u Fin.elim0 = u
theorem Fin.append_left_nil {m : } {n : } {α : Type u_1} (u : Fin mα) (v : Fin nα) (hu : m = 0) :
= v
@[simp]
theorem Fin.elim0_append {n : } {α : Type u_1} (v : Fin nα) :
Fin.append Fin.elim0 v = v
theorem Fin.append_assoc {m : } {n : } {p : } {α : Type u_1} (a : Fin mα) (b : Fin nα) (c : Fin pα) :
theorem Fin.append_left_eq_cons {α : Type u_1} {n : } (x₀ : Fin 1α) (x : Fin nα) :
Fin.append x₀ x = Fin.cons (x₀ 0) x

Appending a one-tuple to the left is the same as Fin.cons.

theorem Fin.cons_eq_append {n : } {α : Type u_1} (x : α) (xs : Fin nα) :
Fin.cons x xs = Fin.append (Fin.cons x Fin.elim0) xs

Fin.cons is the same as appending a one-tuple to the left.

@[simp]
theorem Fin.append_cast_left {n : } {m : } {α : Type u_1} (xs : Fin nα) (ys : Fin mα) (n' : ) (h : n' = n) :
Fin.append (xs ) ys = Fin.append xs ys
@[simp]
theorem Fin.append_cast_right {n : } {m : } {α : Type u_1} (xs : Fin nα) (ys : Fin mα) (m' : ) (h : m' = m) :
Fin.append xs (ys ) = Fin.append xs ys
theorem Fin.append_rev {m : } {n : } {α : Type u_1} (xs : Fin mα) (ys : Fin nα) (i : Fin (m + n)) :
Fin.append xs ys i.rev = Fin.append (ys Fin.rev) (xs Fin.rev) (Fin.cast i)
theorem Fin.append_comp_rev {m : } {n : } {α : Type u_1} (xs : Fin mα) (ys : Fin nα) :
Fin.append xs ys Fin.rev = Fin.append (ys Fin.rev) (xs Fin.rev)
def Fin.repeat {n : } {α : Type u_1} (m : ) (a : Fin nα) :
Fin (m * n)α

Repeat a m times. For example Fin.repeat 2 ![0, 3, 7] = ![0, 3, 7, 0, 3, 7].

Equations
Instances For
@[simp]
theorem Fin.repeat_apply {m : } {n : } {α : Type u_1} (a : Fin nα) (i : Fin (m * n)) :
Fin.repeat m a i = a i.modNat
@[simp]
theorem Fin.repeat_zero {n : } {α : Type u_1} (a : Fin nα) :
= Fin.elim0
@[simp]
theorem Fin.repeat_one {n : } {α : Type u_1} (a : Fin nα) :
= a
theorem Fin.repeat_succ {n : } {α : Type u_1} (a : Fin nα) (m : ) :
@[simp]
theorem Fin.repeat_add {n : } {α : Type u_1} (a : Fin nα) (m₁ : ) (m₂ : ) :
Fin.repeat (m₁ + m₂) a = Fin.append (Fin.repeat m₁ a) (Fin.repeat m₂ a)
theorem Fin.repeat_rev {m : } {n : } {α : Type u_1} (a : Fin nα) (k : Fin (m * n)) :
Fin.repeat m a k.rev = Fin.repeat m (a Fin.rev) k
theorem Fin.repeat_comp_rev {m : } {n : } {α : Type u_1} (a : Fin nα) :
Fin.rev = Fin.repeat m (a Fin.rev)

In the previous section, we have discussed inserting or removing elements on the left of a tuple. In this section, we do the same on the right. A difference is that Fin (n+1) is constructed inductively from Fin n starting from the left, not from the right. This implies that Lean needs more help to realize that elements belong to the right types, i.e., we need to insert casts at several places.

def Fin.init {n : } {α : Fin (n + 1)Type u} (q : (i : Fin (n + 1)) → α i) (i : Fin n) :
α i.castSucc

The beginning of an n+1 tuple, i.e., its first n entries

Equations
Instances For
theorem Fin.init_def {n : } {α : Fin (n + 1)Type u_1} {q : (i : Fin (n + 1)) → α i} :
(Fin.init fun (k : Fin (n + 1)) => q k) = fun (k : Fin n) => q k.castSucc
def Fin.snoc {n : } {α : Fin (n + 1)Type u} (p : (i : Fin n) → α i.castSucc) (x : α (Fin.last n)) (i : Fin (n + 1)) :
α i

Adding an element at the end of an n-tuple, to get an n+1-tuple. The name snoc comes from cons (i.e., adding an element to the left of a tuple) read in reverse order.

Equations
Instances For
@[simp]
theorem Fin.init_snoc {n : } {α : Fin (n + 1)Type u} (x : α (Fin.last n)) (p : (i : Fin n) → α i.castSucc) :
@[simp]
theorem Fin.snoc_castSucc {n : } {α : Fin (n + 1)Type u} (x : α (Fin.last n)) (p : (i : Fin n) → α i.castSucc) (i : Fin n) :
Fin.snoc p x i.castSucc = p i
@[simp]
theorem Fin.snoc_comp_castSucc {n : } {α : Type u_1} {a : α} {f : Fin nα} :
Fin.snoc f a Fin.castSucc = f
@[simp]
theorem Fin.snoc_last {n : } {α : Fin (n + 1)Type u} (x : α (Fin.last n)) (p : (i : Fin n) → α i.castSucc) :
Fin.snoc p x (Fin.last n) = x
theorem Fin.snoc_zero {α : Type u_1} (p : Fin 0α) (x : α) :
Fin.snoc p x = fun (x_1 : Fin (0 + 1)) => x
@[simp]
theorem Fin.snoc_comp_nat_add {n : } {m : } {α : Type u_1} (f : Fin (m + n)α) (a : α) :
@[simp]
theorem Fin.snoc_cast_add {m : } {n : } {α : Fin (n + m + 1)Type u_1} (f : (i : Fin (n + m)) → α i.castSucc) (a : α (Fin.last (n + m))) (i : Fin n) :
Fin.snoc f a (Fin.castAdd (m + 1) i) = f (Fin.castAdd m i)
@[simp]
theorem Fin.snoc_comp_cast_add {n : } {m : } {α : Type u_1} (f : Fin (n + m)α) (a : α) :
Fin.snoc f a Fin.castAdd (m + 1) = f
@[simp]
theorem Fin.snoc_update {n : } {α : Fin (n + 1)Type u} (x : α (Fin.last n)) (p : (i : Fin n) → α i.castSucc) (i : Fin n) (y : α i.castSucc) :
Fin.snoc (Function.update p i y) x = Function.update (Fin.snoc p x) i.castSucc y

Updating a tuple and adding an element at the end commute.

theorem Fin.update_snoc_last {n : } {α : Fin (n + 1)Type u} (x : α (Fin.last n)) (p : (i : Fin n) → α i.castSucc) (z : α (Fin.last n)) :

Adding an element at the beginning of a tuple and then updating it amounts to adding it directly.

@[simp]
theorem Fin.snoc_init_self {n : } {α : Fin (n + 1)Type u} (q : (i : Fin (n + 1)) → α i) :
Fin.snoc (Fin.init q) (q (Fin.last n)) = q

Concatenating the first element of a tuple with its tail gives back the original tuple

@[simp]
theorem Fin.init_update_last {n : } {α : Fin (n + 1)Type u} (q : (i : Fin (n + 1)) → α i) (z : α (Fin.last n)) :

Updating the last element of a tuple does not change the beginning.

@[simp]
theorem Fin.init_update_castSucc {n : } {α : Fin (n + 1)Type u} (q : (i : Fin (n + 1)) → α i) (i : Fin n) (y : α i.castSucc) :

Updating an element and taking the beginning commute.

theorem Fin.tail_init_eq_init_tail {n : } {β : Type u_1} (q : Fin (n + 2)β) :

tail and init commute. We state this lemma in a non-dependent setting, as otherwise it would involve a cast to convince Lean that the two types are equal, making it harder to use.

theorem Fin.cons_snoc_eq_snoc_cons {n : } {β : Type u_1} (a : β) (q : Fin nβ) (b : β) :

cons and snoc commute. We state this lemma in a non-dependent setting, as otherwise it would involve a cast to convince Lean that the two types are equal, making it harder to use.

theorem Fin.comp_snoc {n : } {α : Type u_1} {β : Type u_2} (g : αβ) (q : Fin nα) (y : α) :
g Fin.snoc q y = Fin.snoc (g q) (g y)
theorem Fin.append_right_eq_snoc {α : Type u_1} {n : } (x : Fin nα) (x₀ : Fin 1α) :
Fin.append x x₀ = Fin.snoc x (x₀ 0)

Appending a one-tuple to the right is the same as Fin.snoc.

theorem Fin.snoc_eq_append {n : } {α : Type u_1} (xs : Fin nα) (x : α) :
Fin.snoc xs x = Fin.append xs (Fin.cons x Fin.elim0)

Fin.snoc is the same as appending a one-tuple

theorem Fin.append_left_snoc {n : } {m : } {α : Type u_1} (xs : Fin nα) (x : α) (ys : Fin mα) :
theorem Fin.append_right_cons {n : } {m : } {α : Type u_1} (xs : Fin nα) (y : α) (ys : Fin mα) :
theorem Fin.append_cons {m : } {n : } {α : Type u_1} (a : α) (as : Fin nα) (bs : Fin mα) :
theorem Fin.append_snoc {m : } {n : } {α : Type u_1} (as : Fin nα) (bs : Fin mα) (b : α) :
theorem Fin.comp_init {n : } {α : Type u_1} {β : Type u_2} (g : αβ) (q : Fin n.succα) :
g = Fin.init (g q)
@[inline]
def Fin.snocCases {n : } {α : Fin (n + 1)Type u} {P : ((i : Fin n.succ) → α i)Sort u_1} (h : (xs : (i : Fin n) → α i.castSucc) → (x : α (Fin.last n)) → P (Fin.snoc xs x)) (x : (i : Fin n.succ) → α i) :
P x

Recurse on an n+1-tuple by splitting it its initial n-tuple and its last element.

Equations
Instances For
@[simp]
theorem Fin.snocCases_snoc {n : } {α : Fin (n + 1)Type u} {P : ((i : Fin (n + 1)) → α i)Sort u_1} (h : (x : (i : Fin n) → α i.castSucc) → (x₀ : α (Fin.last n)) → P (Fin.snoc x x₀)) (x : (i : Fin n) → Fin.init α i) (x₀ : α (Fin.last n)) :
Fin.snocCases h (Fin.snoc x x₀) = h x x₀
def Fin.snocInduction {α : Type u_1} {P : {n : } → (Fin nα)Sort u_2} (h0 : P Fin.elim0) (h : {n : } → (x : Fin nα) → (x₀ : α) → P xP (Fin.snoc x x₀)) {n : } (x : Fin nα) :
P x

Recurse on a tuple by splitting into Fin.elim0 and Fin.snoc.

Equations
Instances For
def Fin.succAboveCases {n : } {α : Fin (n + 1)Sort u} (i : Fin (n + 1)) (x : α i) (p : (j : Fin n) → α (i.succAbove j)) (j : Fin (n + 1)) :
α j

Define a function on Fin (n + 1) from a value on i : Fin (n + 1) and values on each Fin.succAbove i j, j : Fin n. This version is elaborated as eliminator and works for propositions, see also Fin.insertNth for a version without an @[elab_as_elim] attribute.

Equations
• i.succAboveCases x p j = if hj : j = i then x else if hlt : j < i then Eq.recOn (p (j.castPred )) else Eq.recOn (p (j.pred ))
Instances For
theorem Fin.forall_iff_succAbove {n : } {p : Fin (n + 1)Prop} (i : Fin (n + 1)) :
(∀ (j : Fin (n + 1)), p j) p i ∀ (j : Fin n), p (i.succAbove j)
def Fin.removeNth {n : } {α : Fin (n + 1)Type u} (p : Fin (n + 1)) (f : (i : Fin (n + 1)) → α i) (i : Fin n) :
α (p.succAbove i)

Remove the p-th entry of a tuple.

Equations
• p.removeNth f i = f (p.succAbove i)
Instances For
def Fin.insertNth {n : } {α : Fin (n + 1)Type u} (i : Fin (n + 1)) (x : α i) (p : (j : Fin n) → α (i.succAbove j)) (j : Fin (n + 1)) :
α j

Insert an element into a tuple at a given position. For i = 0 see Fin.cons, for i = Fin.last n see Fin.snoc. See also Fin.succAboveCases for a version elaborated as an eliminator.

Equations
• i.insertNth x p j = i.succAboveCases x p j
Instances For
@[simp]
theorem Fin.insertNth_apply_same {n : } {α : Fin (n + 1)Type u} (i : Fin (n + 1)) (x : α i) (p : (j : Fin n) → α (i.succAbove j)) :
i.insertNth x p i = x
@[simp]
theorem Fin.insertNth_apply_succAbove {n : } {α : Fin (n + 1)Type u} (i : Fin (n + 1)) (x : α i) (p : (j : Fin n) → α (i.succAbove j)) (j : Fin n) :
i.insertNth x p (i.succAbove j) = p j
@[simp]
@[simp]
theorem Fin.removeNth_insertNth {n : } {α : Fin (n + 1)Type u} (p : Fin (n + 1)) (a : α p) (f : (i : Fin n) → α (p.succAbove i)) :
p.removeNth (p.insertNth a f) = f
@[simp]
theorem Fin.removeNth_zero {n : } {α : Fin (n + 1)Type u} (f : (i : Fin (n + 1)) → α i) :
=
@[simp]
theorem Fin.removeNth_last {n : } {α : Type u_1} (f : Fin (n + 1)α) :
(Fin.last n).removeNth f =
@[simp]
theorem Fin.insertNth_comp_succAbove {n : } {β : Type v} (i : Fin (n + 1)) (x : β) (p : Fin nβ) :
i.insertNth x p i.succAbove = p
theorem Fin.insertNth_eq_iff {n : } {α : Fin (n + 1)Type u} {p : Fin (n + 1)} {a : α p} {f : (i : Fin n) → α (p.succAbove i)} {g : (j : Fin (n + 1)) → α j} :
p.insertNth a f = g a = g p f = p.removeNth g
theorem Fin.eq_insertNth_iff {n : } {α : Fin (n + 1)Type u} {p : Fin (n + 1)} {a : α p} {f : (i : Fin n) → α (p.succAbove i)} {g : (j : Fin (n + 1)) → α j} :
g = p.insertNth a f g p = a p.removeNth g = f
theorem Fin.insertNth_apply_below {n : } {α : Fin (n + 1)Type u} {i : Fin (n + 1)} {j : Fin (n + 1)} (h : j < i) (x : α i) (p : (k : Fin n) → α (i.succAbove k)) :
i.insertNth x p j = Eq.recOn (p (j.castPred ))
theorem Fin.insertNth_apply_above {n : } {α : Fin (n + 1)Type u} {i : Fin (n + 1)} {j : Fin (n + 1)} (h : i < j) (x : α i) (p : (k : Fin n) → α (i.succAbove k)) :
i.insertNth x p j = Eq.recOn (p (j.pred ))
theorem Fin.insertNth_zero {n : } {α : Fin (n + 1)Type u} (x : α 0) (p : (j : Fin n) → α (Fin.succAbove 0 j)) :
= Fin.cons x fun (j : Fin n) => cast (p j)
@[simp]
theorem Fin.insertNth_zero' {n : } {β : Type v} (x : β) (p : Fin nβ) :
= Fin.cons x p
theorem Fin.insertNth_last {n : } {α : Fin (n + 1)Type u} (x : α (Fin.last n)) (p : (j : Fin n) → α ((Fin.last n).succAbove j)) :
(Fin.last n).insertNth x p = Fin.snoc (fun (j : Fin n) => cast (p j)) x
@[simp]
theorem Fin.insertNth_last' {n : } {β : Type v} (x : β) (p : Fin nβ) :
(Fin.last n).insertNth x p = Fin.snoc p x
theorem Fin.insertNth_rev {n : } {α : Type u_1} (i : Fin (n + 1)) (a : α) (f : Fin nα) (j : Fin (n + 1)) :
i.insertNth a f j.rev = i.rev.insertNth a (f Fin.rev) j
theorem Fin.insertNth_comp_rev {n : } {α : Type u_1} (i : Fin (n + 1)) (x : α) (p : Fin nα) :
i.insertNth x p Fin.rev = i.rev.insertNth x (p Fin.rev)
theorem Fin.cons_rev {α : Type u_1} {n : } (a : α) (f : Fin nα) (i : Fin (n + 1)) :
Fin.cons a f i.rev = Fin.snoc (f Fin.rev) a i
theorem Fin.cons_comp_rev {α : Type u_1} {n : } (a : α) (f : Fin nα) :
Fin.cons a f Fin.rev = Fin.snoc (f Fin.rev) a
theorem Fin.snoc_rev {α : Type u_1} {n : } (a : α) (f : Fin nα) (i : Fin (n + 1)) :
Fin.snoc f a i.rev = Fin.cons a (f Fin.rev) i
theorem Fin.snoc_comp_rev {α : Type u_1} {n : } (a : α) (f : Fin nα) :
Fin.snoc f a Fin.rev = Fin.cons a (f Fin.rev)
theorem Fin.insertNth_binop {n : } {α : Fin (n + 1)Type u} (op : (j : Fin (n + 1)) → α jα jα j) (i : Fin (n + 1)) (x : α i) (y : α i) (p : (j : Fin n) → α (i.succAbove j)) (q : (j : Fin n) → α (i.succAbove j)) :
(i.insertNth (op i x y) fun (j : Fin n) => op (i.succAbove j) (p j) (q j)) = fun (j : Fin (n + 1)) => op j (i.insertNth x p j) (i.insertNth y q j)
theorem Fin.insertNth_le_iff {n : } {α : Fin (n + 1)Type u} [(i : Fin (n + 1)) → Preorder (α i)] {i : Fin (n + 1)} {x : α i} {p : (j : Fin n) → α (i.succAbove j)} {q : (j : Fin (n + 1)) → α j} :
i.insertNth x p q x q i p fun (j : Fin n) => q (i.succAbove j)
theorem Fin.le_insertNth_iff {n : } {α : Fin (n + 1)Type u} [(i : Fin (n + 1)) → Preorder (α i)] {i : Fin (n + 1)} {x : α i} {p : (j : Fin n) → α (i.succAbove j)} {q : (j : Fin (n + 1)) → α j} :
q i.insertNth x p q i x (fun (j : Fin n) => q (i.succAbove j)) p
@[simp]
theorem Fin.removeNth_update {n : } {α : Fin (n + 1)Type u} (p : Fin (n + 1)) (x : α p) (f : (j : Fin (n + 1)) → α j) :
p.removeNth (Function.update f p x) = p.removeNth f
@[simp]
theorem Fin.insertNth_removeNth {n : } {α : Fin (n + 1)Type u} (p : Fin (n + 1)) (x : α p) (f : (j : Fin (n + 1)) → α j) :
p.insertNth x (p.removeNth f) =
theorem Fin.insertNth_self_removeNth {n : } {α : Fin (n + 1)Type u} (p : Fin (n + 1)) (f : (j : Fin (n + 1)) → α j) :
p.insertNth (f p) (p.removeNth f) = f
@[deprecated Fin.removeNth]
def Fin.extractNth {n : } {α : Fin (n + 1)Type u} (i : Fin (n + 1)) (f : (j : Fin (n + 1)) → α j) :
α i × ((j : Fin n) → α (i.succAbove j))

Separates an n+1-tuple, returning a selected index and then the rest of the tuple. Functional form of Equiv.piFinSuccAbove.

Equations
• i.extractNth f = (f i, i.removeNth f)
Instances For
def Fin.find {n : } (p : Fin nProp) [] :

find p returns the first index n where p n is satisfied, and none if it is never satisfied.

Equations
Instances For
theorem Fin.find_spec {n : } (p : Fin nProp) [] {i : Fin n} :
i p i

If find p = some i, then p i holds

theorem Fin.isSome_find_iff {n : } {p : Fin nProp} [] :
(Fin.find p).isSome = true ∃ (i : Fin n), p i

find p does not return none if and only if p i holds at some index i.

theorem Fin.find_eq_none_iff {n : } {p : Fin nProp} [] :
= none ∀ (i : Fin n), ¬p i

find p returns none if and only if p i never holds.

theorem Fin.find_min {n : } {p : Fin nProp} [] {i : Fin n} :
i ∀ {j : Fin n}, j < i¬p j

If find p returns some i, then p j does not hold for j < i, i.e., i is minimal among the indices where p holds.

theorem Fin.find_min' {n : } {p : Fin nProp} [] {i : Fin n} (h : i ) {j : Fin n} (hj : p j) :
i j
theorem Fin.nat_find_mem_find {n : } {p : Fin nProp} [] (h : ∃ (i : ) (hin : i < n), p i, hin) :
,
theorem Fin.mem_find_iff {n : } {p : Fin nProp} [] {i : Fin n} :
i p i ∀ (j : Fin n), p ji j
theorem Fin.find_eq_some_iff {n : } {p : Fin nProp} [] {i : Fin n} :
= some i p i ∀ (j : Fin n), p ji j
theorem Fin.mem_find_of_unique {n : } {p : Fin nProp} [] (h : ∀ (i j : Fin n), p ip ji = j) {i : Fin n} (hi : p i) :
i
def Fin.contractNth {n : } {α : Type u_1} (j : Fin (n + 1)) (op : ααα) (g : Fin (n + 1)α) (k : Fin n) :
α

Sends (g₀, ..., gₙ) to (g₀, ..., op gⱼ gⱼ₊₁, ..., gₙ).

Equations
• j.contractNth op g k = if k < j then g k.castSucc else if k = j then op (g k.castSucc) (g k.succ) else g k.succ
Instances For
theorem Fin.contractNth_apply_of_lt {n : } {α : Type u_1} (j : Fin (n + 1)) (op : ααα) (g : Fin (n + 1)α) (k : Fin n) (h : k < j) :
j.contractNth op g k = g k.castSucc
theorem Fin.contractNth_apply_of_eq {n : } {α : Type u_1} (j : Fin (n + 1)) (op : ααα) (g : Fin (n + 1)α) (k : Fin n) (h : k = j) :
j.contractNth op g k = op (g k.castSucc) (g k.succ)
theorem Fin.contractNth_apply_of_gt {n : } {α : Type u_1} (j : Fin (n + 1)) (op : ααα) (g : Fin (n + 1)α) (k : Fin n) (h : j < k) :
j.contractNth op g k = g k.succ
theorem Fin.contractNth_apply_of_ne {n : } {α : Type u_1} (j : Fin (n + 1)) (op : ααα) (g : Fin (n + 1)α) (k : Fin n) (hjk : j k) :
j.contractNth op g k = g (j.succAbove k)
theorem Fin.sigma_eq_of_eq_comp_cast {α : Type u_1} {a : (ii : ) × (Fin iiα)} {b : (ii : ) × (Fin iiα)} (h : a.fst = b.fst) :
a.snd = b.snd a = b

To show two sigma pairs of tuples agree, it to show the second elements are related via Fin.cast.

theorem Fin.sigma_eq_iff_eq_comp_cast {α : Type u_1} {a : (ii : ) × (Fin iiα)} {b : (ii : ) × (Fin iiα)} :
a = b ∃ (h : a.fst = b.fst), a.snd = b.snd

Fin.sigma_eq_of_eq_comp_cast as an iff.